Certeza legal e inversión extranjera en África: llamemos la unión africana (2016)
This article studies the role of the African Union (AU) as an instrument for providing legal certainty to foreign investors in the African continent. Africa has failed to attract foreign investment since the business environment and market conditions do not even appeal to national investors. One of the biggest problems contributing to this situation is a low level of legal certainty which makes it too risky for foreign investors to invest in the region. Therefore, the development and adoption of policies and actions aimed at the provision of a higher level of legal certainty is necessary. This article precisely proposes the usage of the AU as an instrument to achieve this goal. This regional integrationist experience groups several elements that can positively contribute to the provision of legal certainty to foreign investors. For instance, it has an institutional structure that allows its institutions to work coordinately in the adoption of policies and laws, which makes possible the development and adoption of coherent and stable laws and policies. Likewise, the AU’s structure allows the exchange of opinions, ideas, and experiences between African governments and foreign investors during the decision-making process by means of an institution such as ECOSOCC and the private sector Forum. This communication promotes transparency and predictability to foreign investors for the development of their economic activities. In addition, AU also has the power to create legal instruments that serve to regulate the activity of foreign investors, limiting the power of the host country to interfere in the investment, and promote the progress and respect of matters such as the rule of law, transparency and good governance in the continent. Moreover, the AU has its own judicial body that works to enforce the AU legal instruments and guarantees their fulfillment by member countries.This article studies the role of the African Union (AU) as an instrument for providing legal certainty to foreign investors in the region. Africa is a region characterized by a low level of foreign investment. The continent has failed to attract foreign investors since the business environment and market conditions do not even appeal to national investors